Uranium. No. 05. Interview with John Fleming and Norman Kipnis - Memorial University of Newfoundland. Extension Service (Community Learning Centre, 1977)
John Flemming and Norman Kipnis of the Provincial Department of Mines and Energy discuss various aspects of worker health and safety at the proposed Brinex uranium devleopment in Labrador.